Arhitekturna dimenzija dela na daljavo - Kovačič, Iztok (Urbani izziv, 2005)
The computer has become an integral part of our environment. With the integration of information and communication technologies into the working process the organization of office work is rapidly changing, influencing the office spaces as well as office buildings. The continuous evolution of sophisticated and mobile devices, developed as a result of information and communication revolution, enables us not only to work in the office but also at home, on the train, in hotels or even on the beach, in the park. The commonname for this kind of activity is teleworking. One of the latest varieties is the combination of mobile work and home office that was called Sharing office. The workers usually perform most of their tasks at home and only come to office for briefings, meetings or similar kind of operation. The office building of the future will therefore be created with the purpose to connect and unite workers for common tasks and reconciliation. It will become the center point for people to meet and communicate. Architecture will therefore take upon itself the catalyst function.
Keywords: architecture; arhitektura; delo na daljavo; informacijska tehnologija; information technology; organizacija dela; pisarne; poslovne zgradbe; projektiranje